Evaluation of menstrual irregularities and dysmenorrhea in university students - POTUR, DİLEK (My University, 2022)
Purpose: Menstruation takes an important place in women's lives all over the world. For this reason, problems such as menstrual irregularities and dysmenorrhea affect women's lives in many ways. Our study aims to determine the factors associated with menstrual irregularities and dysmenorrhea. Materials and methods: It is a cross-sectional study. 1807 students participated. The study was carried out in 2017. The data were collected with the personal ınformation form developed by reviewing the literature. Descriptive statistics such as mean, standard deviation, percentage and logistic regression analysis were used in the study. Results: The average age of the students was 20.33±1.83 and the average age of menarche was 13.41±1.25. 93.5% were single and 66.5% had BMI within normal limits. The majority of the students did not have regular smoking (82%) and exercise habits (73.4%). 23.7% of the students reported menstrual irregularities and 40.5% reported dysmenorrhea. In addition to being overweight, not exercising regularly, caffeine and smoking habits, being single factors were found to be associated with menstrual irregularity. Factors such as being overweight, history of dysmenorrhea in the mother, and lack of exercise habits were also found to be associated with dysmenorrhea. Conclusion: The rates of menstrual irregularities and dysmenorrhea in university students of reproductive age are not to be underestimated. It is recommended to conduct intervention studies for interchangeable factors such as regular exercise and BMI associated with these problems.
Keywords: Hemşirelik; Kadın Hastalıkları ve Doğum Hemşireliği; Sağlık Bilimleri; Nursing; Gynecology and Obstetrics Nursing; Health Sciences; Klinik Tıp (MED); Klinik Tıp; HEMŞİRELİK; Clinical Medicine (MED); CLINICAL MEDICINE; NURSING; Farmakoloji (hemşirelik); Onkoloji (hemşirelik); Asistan Hemşirelik; Tıbbi ve Cerrahi Hemşirelik; Annelik ve Ebelik; LPN ve LVN; Acil Tıp Hemşireliği; Yoğun Bakım Hemşireliği; İleri ve Uzman Hemşirelik; Hemşirelik (çeşitli); Genel Hemşirelik; Pharmacology (nursing); Oncology (nursing); Nurse Assisting; Medical and Surgical Nursing; Maternity and Midwifery; LPN and LVN; Emergency Nursing; Critical Care Nursing; Advanced and Specialized Nursing; Nursing (miscellaneous); General Nursing; Menstruation; dysmenorrhea; students